Rutin bioconjugates as potential nutraceutical prodrugs: An in vitro and in ovo toxicological screening - Dehelean, Cristina Adriana; Coricovac, Dorina; Pinzaru, Iulia; Marcovici, Iasmina; Macasoi, Ioana Gabriela; Semenescu, Alexandra; Lazar, Geza; Cinta Pinzaru, Simona; Radulov, Isidora; Alexa, Ersilia; Cretu, Octavian (Frontiers in Pharmacology, 2022)
Rutin (RUT) is considered one the most attractive flavonoids from a therapeutic perspective due to its multispectral pharmacological activities including antiradical, anti-inflammatory, antiproliferative, and antimetastatic among others. Still, this compound presents a low bioavailability what narrows its clinical applications. To overcome this inconvenience, the current paper was focused on the synthesis, characterization, and toxicological assessment of two RUT bioconjugates obtained by enzymatic esterification with oleic acid (OA) and linoleic acid (LA) - rutin oleate (RUT-O) and rutin linoleate (RUT-L), as flavonoid precursors with improved physicochemical and biological properties. Following the enzymatic synthesis in the presence of Novozyme® 435, the two bioconjugates were obtained, their formation being confirmed by RAMAN and FT-IR spectroscopy. The in vitro and in ovo toxicological assessment of RUT bioconjugates (1-100 µM) was performed using 2D consecrated cell lines (cardiomyoblasts - H9C2(2-1), hepatocytes – HepaRG, and keratinocytes – HaCaT), 3D reconstructed human epidermis tissue (EpiDerm™), and chick chorioallantoic membranes, respectively. The results obtained were test compound, concentration – and cell-type dependent, as follows: RUT-O reduced the viability of H9c2(2-1), HepaRG, and HaCaT cells at 100 µM (to 77.53%, 83.17%, and 78.32%, respectively), and induced cell rounding and floating, as well as apoptotic-like features in the nuclei of all cell lines, whereas RUT-L exerted no signs of cytotoxicity in all cell lines in terms of cell viability, morphology, and nuclear integrity. Both RUT esters impaired the migration of HepaRG cells (at 25 µM) and lack irritative potential (at 100 µM) in vitro (tissue viability >50%) and in ovo (irritation scores of 0.70 for RUT-O, and 0.49 for RUT-L, respectively). Computational predictions revealed an increased lipophilicity, and reduced solubility, drug-likeness and drug score of RUT-O and RUT-L compared to their parent compounds – RUT, OA, and LA. In conclusion, we report a favorable toxicological profile for RUT-L, while RUT-O is dosage-limited since at high concentrations were noticed cytotoxic effects.